How does the added fat source affect sensory quality of sheep and goat pâtés? - Rodrigues, Sandra (2018)
Sensory quality of sheep and goat pâtés with different sources and percentage of fat (10% or 30%, and pork belly or olive oil) were evaluated. A trained taste panel performed sensory analysis and consumers were consulted to perceive their preferences. Generalised Procrustes Analysis was used to test the differences found by panellists. Panellists were able to find sensory differences between sheep and goat pâtés, and also fat percentages. Goat pâtés had higher values of juiciness and sheep pâtés had higher values of taste intensity. Ten percent pork belly fat pâtés had the highest values of colour and cohesiveness attributes and also aroma intensity, while 30% olive oil pâtés had the highest values of texture attributes, except cohesiveness. Although, differences between pâtés were found by panellists, consumers had no particular preference for one of them.